Ethical Conundrums in Fatality Review Planning, Data Collection, and Reporting: Viewing the Work of Review Teams Through the Lens of Evaluation. (November 2013) - Albright, Danielle; Banks, Laura; Broidy, Lisa; Crandall, Cameron; Campos, Gabriel
The multidisciplinary, interprofessional practice of fatality review is quickly becoming more methodologically sophisticated. However, the discussion of ethical issues related to fatality review has been limited to the topics of confidentiality and the ethical guidelines of participant professions. We propose that the work of fatality review teams is similar to the research practice of evaluation. Using the Guiding Principles of Evaluation recommended by the American Evaluation Association (AEA), this paper begins an exploration of potential ethical conundrums faced by domestic violence fatality review teams and identifies suggestions for ensuring that the teams have the necessary tools for ethical practice.